2020
DOI: 10.14710/izumi.9.1.58-74
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Discourse Analysis of The Advertisement of Japanese Beauty Products

Abstract: This research analyzes the advertisement of Japanese beauty products through perspective of the critical discourse analysis as stated by Fairclough (1995). The discussed issues are linguistic features used in the advertisement of Japanese beauty products and the strategies used by advertisers to manipulate consumers who are women. Through three dimensions of the critical discourse analysis, it is known that the choices of vocabularies, grammar, modality, and rhetoric serve to bring psychological effect to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…In advertising, positive adjectives are commonly used to ensure potential customers can remember the product's benefits. For example, cosmetic advertisements often use positive adjectives that promise physical changes desired by consumers as a result of using the promoted beauty product (Kaur et al, 2013;Lestari, 2020;Susanti, 2019). However, in Garnier Green Beauty advertisements, positive adjectives highlight the benefits of using green cosmetics for the environment.…”
Section: What Linguistic Features and Discourse Strategies Are Used I...mentioning
confidence: 99%
See 1 more Smart Citation
“…In advertising, positive adjectives are commonly used to ensure potential customers can remember the product's benefits. For example, cosmetic advertisements often use positive adjectives that promise physical changes desired by consumers as a result of using the promoted beauty product (Kaur et al, 2013;Lestari, 2020;Susanti, 2019). However, in Garnier Green Beauty advertisements, positive adjectives highlight the benefits of using green cosmetics for the environment.…”
Section: What Linguistic Features and Discourse Strategies Are Used I...mentioning
confidence: 99%
“…Additionally, the advertisements often employ a problem-solution formula, in which the promoted products solve the consumers' problems with their physical appearance (Kaur et al, 2013). Another common feature of cosmetics advertisements is celebrity endorsement, portraying the ideal image that the customers can attain or associate with by using the promoted products (Kaur et al, 2013;Lestari, 2020;Raharjo et al, 2020;Susanti, 2019). Also, they often use scientific claims to convince the customers (Kaur et al, 2013;Kenalemang-Palm & Eriksson, 2021;Lestari, 2020;Susanti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A discourse can affect and be influenced by social context. Fairlclough described discourse as a form of "social practice" which implicates the existence of dialectics between language and social conditions (cited in Lestari, 2020). In the eye glasses critical discourse analysis, according to Fairlclough and Wodak (cited in Van Dijk, 1977) the practice of discourse could be display ideology: it can produce unbalanced power relationships between social classes, men and women, majority groups and minorities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the analysis of discourse in Japanese beauty product, certain discourse used as strategies by advertisers to manipulate consumers for purchasing their product. Those strategies can be exaggerating their quality or playing with the emotion of consumers (Lestari, 2020). While the analysis about the Advertising Discourse, it was obtained that the discourse in advertisement affect costumer beliefs through discourse and the effectiveness of 2020.…”
Section: Introductionmentioning
confidence: 98%
“…Susanti et.al (2019) in their research about Wacana Kritis Fairclough dalam Teks Iklan Mana Tau: Indian Royal Coffee found that Fairclough's CDA (three dimensions) could help researchers find the ideology and the aim of the advertisement which shows consumptive and modern lifestyle. Comparing to Susanti's, Lestari (2020) explained in her research about A Critical Discourse Analysis of The Advertisement of Japanese Beauty Products that through three dimensions of the critical discourse analysis, the choices of vocabularies, grammar, modality, and rhetoric served to bring psychological effect to consumers and manipulate them to purchase or use the offered products. However, Asnidar (2018) found in her research entitled Analisis Wacana Kritis Iklan Operator Seluler that Fairclough's CDA in analyzing advertisement could also discover experiential, relational, and expressive value through three steps of analysis: description, interpretation, and explanation to see how words are produced.…”
Section: Introductionmentioning
confidence: 99%